Komunitas dan Preferensi Habitat Gastropoda pada Kedalaman Berbeda di Zona Litoral Danau Singkarak Provinsi Sumatera Barat - Wendri, Yuli; Nurdin, Jabang; Zakaria, Indra Junaidi (Metamorfosa: Journal of Biological Sciences; Vol 6 No 1 (2019), 2019)
This research was conducted in Lake Singkarak from February to March 2016, using purposive sampling method in three locations namely Tanjung Mutiara, Malalo and Paninggahan, at a depth of 0.5 m, 1 m and 1.5 m in each location. Samples were collected using 30x30 cm 2  surber net. The result showed four gastropod species from family of Thiaridae, namely  Melanoides granifera ,  Melanoides tuberculata ,  Brotia costula  and  Thiara scabra . Average population density of gastropod in Lake Singkarak was 399.75 ind / m 2 . The population density at depths ranging from 271.11 to 568.89 ind/m 2 , the highest population density is showed at a depth of 1.5 m and the lowest at a depth of 0.5 m.  Melanoides tuberculata  shows highest density at all depths.  M. granifera  prefers habitats with a depth of 1.5 m,  M. tuberculata  prefers a depth of 1 m,  T. scabra  prefers a depth up to 1.5 m and  B. Costula  prefer habitat with a depth of 0.5 m. Condition of Lake Singkarak shows as favorable and suitable habitat for gastropod’s life.